Meningkatkan Karakter Pancasila melalui E-Book Sains Inovatif: Pendekatan Digital untuk Pendidikan Nilai - Zulfikar Zulfikar; Suryanef Suryanef; Fatmariza Fatmariza; Siti Fatimah (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to improve the practice of Pancasila character values through the use of Innovative Science E-Book with digital approach in learning. By integrating Pancasila values into various science topics, this E-Book is expected to strengthen students' understanding of values such as Indonesian Unity, Social Justice, Humanity, God Almighty, and Democracy. The results showed a significant increase in the practice of Pancasila values after the use of the E-Book, especially in the aspects of Indonesian Unity and Social Justice. The E-Book was also considered very suitable for the curriculum, easy to use, and effective in increasing student engagement and understanding. In conclusion, the digital approach through the Innovative Science E-Book proved to be an effective medium in Pancasila character education in schools, making it a relevant and powerful tool in the modern educational context